2018
DOI: 10.1371/journal.pone.0202887
|View full text |Cite
|
Sign up to set email alerts
|

Rapid bioerosion in a tropical upwelling coral reef

Abstract: Coral reefs persist in an accretion-erosion balance, which is critical for understanding the natural variability of sediment production, reef accretion, and their effects on the carbonate budget. Bioerosion (i.e. biodegradation of substrate) and encrustation (i.e. calcified overgrowth on substrate) influence the carbonate budget and the ecological functions of coral reefs, by substrate formation/consolidation/erosion, food availability and nutrient cycling. This study investigates settlement succession and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 63 publications
0
20
1
4
Order By: Relevance
“…Each of the microatolls showed individual macroscopically visible boreholes of 2-3 mm in diameter, presumably caused by macroborers. Numerous studies also confirmed the important role of macroborers for coral erosion, including lithophagine bivalves (Wizemann et al, 2018) and polychaetes (Davies and Hutchings, 1983). While faunal organisms generally contribute substantially to coral erosion (Zubia and Peyrot-Clausade, 2001;Tribollet and Golubic, 2011), they might be less abundant in microatolls as a consequence of increased heat stress (Przeslawski et al, 2008) at the water surface.…”
Section: Influence Of Endolithic Green Algae On Coral Skeletonmentioning
confidence: 91%
See 1 more Smart Citation
“…Each of the microatolls showed individual macroscopically visible boreholes of 2-3 mm in diameter, presumably caused by macroborers. Numerous studies also confirmed the important role of macroborers for coral erosion, including lithophagine bivalves (Wizemann et al, 2018) and polychaetes (Davies and Hutchings, 1983). While faunal organisms generally contribute substantially to coral erosion (Zubia and Peyrot-Clausade, 2001;Tribollet and Golubic, 2011), they might be less abundant in microatolls as a consequence of increased heat stress (Przeslawski et al, 2008) at the water surface.…”
Section: Influence Of Endolithic Green Algae On Coral Skeletonmentioning
confidence: 91%
“…As calcium concentrations are usually strictly controlled in all types of organisms (White and Broadley, 2003;Dominguez, 2004;Brini et al, 2013) due to its toxic effects (Smith, 1995), passive diffusion of Ca 2+ ions within the algal thallus is highly unlikely. Instead, once taken up, the majority of calcium ions might have been attached to calcium-binding proteins acting as concentration buffers (La Verde et al, 2018).…”
Section: Influence Of Endolithic Green Algae On Coral Skeletonmentioning
confidence: 99%
“…These taxa were largely absent in the GoC, but abundant, yet patchily distributed, in the GoP. Exclusively heterotrophic, suspension-feeding fauna rapidly colonize dead-coral substrates in upwelling regions in the ETP (Wizemann et al 2018). They are also relatively fast-growing, as evidenced by balanoid barnacles that have been observed to reach 15 mm in diameter in 56 d in the GoP (Birkeland 1977).…”
Section: Calcificationmentioning
confidence: 99%
“…However, it has also been suggested that upwelling areas do not always guarantee refuge for coral reefs in a warming ocean unless the thermal threat and upwelling coincide [136]. Some large-scale seasonal upwelling with cold, nutrient-rich, and naturally acidic subsurface water-such as the upwelling in Gulf of Panama and Papagayo upwelling of Costa Rica, in the tropical eastern Pacific-indeed hinders the development of coral reefs [137][138][139]. In KNP, upwelling is small-scale, localized, and induced by tides flowing from east to west Nanwan that create a temperature difference within the bay of Nanwan and two sides of Hengchun Peninsula, where the water is cooler in the east and warmer in the west (Table 4).…”
Section: Discussionmentioning
confidence: 99%